PERAN POSYANDU REMAJA TERHADAP SKRINING ANEMIA REMAJA DI WILAYAH PUSKESMAS KRAMAT KABUPATEN TEGAL - Elqy Mei Zumaro (Jurnal Ilmiah Kebidanan Imelda, 2024)
Teenage daughters with anemia problems will experience reduced immunity, disturbed concentration, decreased learning performance, fitness problems, productivity, increased risk of death during childbirth, premature birth, and lower baby weight. Consumption of blood supplement tablets can help prevent anemia. The aim of this study is to find out the role of Posyandu Remaja in preventing teenage girls in the Puskesmas Kramat region from developing anemia by 2024. This kind of research is qualitative, so the data comes from observations, interviews, and documentation. Nine informants are composed of health care personnel, chief cadres, teen cadres and teen princesses. In the work area of Puskesmas Kramat, teenage posyandu plays an important role in preventing anemia in teenage daughters. They act as health service providers (motivators, instructors, facilitators, counsellors), connectors between the community and health workers, provide posyandu locations for program interventions, and encourage adolescents to come to posyande. In the case of teenage daughters who take blood supplement pills, the role and posyandu can give a positive effect. This can reduce the number of cases of anemia.